Awake Intubation Fiberoptic Bronchoscope on Pregnancy Patient Undergo Decompression Laminectomy and Cervical Fusion Stabilization - Saputra, Darmawan Jaya; Senapathi, Tjokorda Gde Agung; Aribawa, I Gusti Ngurah Mahaalit; Ryalino, Christopher (Bali Journal of Anesthesiology, 2019)
The traumatic and ankylosing cervical spine being rare in pregnancy can cause serious problems continuing pregnancy. Extensive neurological involvement which is rapidly progressive due to compression should be considered for immediate decompression. We present a case of a patient in the 19th weeks with diagnosis C5 compression fracture and paracervical abscess C5 et causa suspect TB spondylosis, complaints with paralysis in all four limbs. Surgical intervention was deemed necessary and was performed in the prone position. The early operative treatment and appropriate anaesthetic procedure resulted in good clinical outcome with improvement of neurological recovery.